Development of Read Aloud-Based Video Learning to Improve Early Age Children's Literacy Al-Quran - Nurdiantini Nurdiantini; Zainal Abidin Arief; Masitowati Gatot (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This study aims to develop Read Aloud-based learning videos to improve Early Childhood Literacy at Early Childhood Education Al-Quran Dian Asshobri which is appropriate and effective. The development of Read Aloud-based learning videos was developed with a System-based R & D research model, namely ADDIE. Product feasibility was tested by three experts, namely material experts, instructional design experts, and learning media experts as well as student feasibility tests through one-to-one tests, small-scale and large-scale tests. The sample media in this study were group B students with an age range of 5-6 years. The results showed that the quality of the Read Aloud-based learning videos developed was classified as good (89.71%), good for one-to-one trials (88.67%), good for small groups (90.20%) and very good for large groups (92.76%). Meanwhile, the t_count value is 7.87459 and the t_table value at a significant level of 5% is 2.306004, so t_count > t_table or 7.87459 >2.306004, so h_a is accepted and h_0 is rejected. This means that there is a significant difference in student learning outcomes before and after being given treatment. This shows that the Read Aloud-based learning videos are feasible and effective and can improve student learning outcomes.